Foot problems in people with gout in primary care: baseline findings from a prospective cohort study - Edward Roddy; Sara Muller; Keith Rome; Priyanka Chandratre; Samantha L. Hider; Jane Richardson; Milisa Blagojevic‐Bucknall; Christian D. Mallen (Journal of Foot and Ankle Research, 2015)
Abstract Background Foot problems are common in people with gout yet the prevalence of current foot problems in people with gout and the burden they present to healthcare systems is not known. This cross‐sectional study aimed to determine the prevalence and associations of hallux valgus, foot pain and disability in people with gout, and to assess the frequency with which foot problems lead to consultation with healthcare professionals. Methods Adults registered with 20 general practices who had consulted their GP about gout or been prescribed allopurinol or colchicine in the preceding two years were mailed a questionnaire. Prevalence of hallux valgus, foot pain in the last month, and disabling foot pain in the mailed population were ascertained using validated instruments and estimated by inverse‐weighted logistic regression. Associations with socio‐demographic, comorbid and gout‐specific factors were examined using logistic regression. Participants were asked if they had seen health care professionals for foot problems within the preceding 12 months. Results One thousand one hundred eighty‐four questionnaires were received (response 66 %). Prevalence of hallux valgus was 36.3 %, foot pain in the last month 22.3 % and disabling foot pain 14.5 %. Hallux valgus associated with age (adjusted OR 1.47 per 10‐year increase, 95 % CI 1.26, 1.72) and female gender (2.03; 1.31, 3.15). Foot pain in the last month associated with age (1.24; 1.00, 1.55), obesity (BMI 30.0–34.9 2.67; 1.32, 5.38; BMI ≥ 35.0 3.16; 1.44, 6.93), mild depression (2.04; 1.09, 3.81) and polyarticular gout attacks (1.86; 1.18, 2.95). Disabling foot pain associated with age (1.42; 1.08, 1.87), obesity (BMI 30.0–34.9 3.73; 1.54, 9.09; BMI ≥ 35.0 4.36; 1.64, 11.64), depression (mild 2.63; 1.25, 5.53; moderate 3.53; 1.11, 11.26) and ischaemic heart disease (2.45; 1.32, 4.53). In the previous 12 months, 495 (42.8 %) reported consulting their GP about their feet and 281 (23.7 %) a podiatrist/chiropodist. Conclusions Foot problems are common in people with gout and frequently lead to healthcare consultation. Hallux valgus has similar associations to those seen in the general population, whereas foot pain associates with obesity and gout characteristics, and disabling foot pain with obesity and comorbidity. Patient assessment should consider foot problems and offer specific treatment where relevant.